Salt Production in Central Italy and Social Network Analysis Centrality Measures: An Exploratory Approach - Fulminante, F; Alessandri, L (De Gruyter, 2024)
In this work, we study salt-production settlement in central Italy with an exploratory application of centrality indexes, common in social network analysis: betweenness centrality, closeness centrality, and degree centrality. These methods are not new, but they have never been applied to this type of site and the results are innovative and illuminating. In fact, the closeness and degree centrality do not yield particularly interesting results. However, the betweenness centrality, which indicates the most commonly used routes in a given region, provide powerful insights. By indicating shifting most common routes through time, from the terrestrial and sea route along the coast in the Bronze and Iron Age, to the use of the Tiber River and Tiber valley as route, in the Orientalizing and Archaic Period, they allow us to advance hypotheses about the shift between two different productions. The briquetage salt production technique was used in the Bronze and Iron Age on the costal sites, which was also the most common route used in the region. While the proper marine production at the mouth of the Tiber, both on the Etruscan and Latin side, might develop during the Orientalizing and Archaic Age, together with an intensified use of the Via Salaria, running from the coast to the mountains of Latium, along the Tiber River. It would be interesting to confirm these hypotheses with further analyses and also targeted excavations.